CARBON NANOTUBES: A PROMISING TOOL IN DRUG DELIVERY - B. BASU; GUNJAN KUMAR MEHTA (International Journal of Pharma and Bio Sciences, 2014)
Nanomaterials are at the leading edge of the rapidly developing field of nanotechnology. Their unique size-dependent properties make these materials superior and indispensable in many areas of human activity. Carbon nanotubes (CNTs) have recently garnered interest of today’s world of medicine and are being highly researched in the fields of efficient drug delivery and biosensing methods for disease treatment and health monitoring. Nanotubes are categorized as single-walled carbon nanotubes (SWCNTS) and multiple walled carbon nanotubes (MWCNTS). Various techniques have been developed to produce carbon nanotubes in sizeable quantities, including arc discharge, laser ablation, chemical vapor deposition, silane solution method and flame synthesis method. Research on properties and characteristics of CNTs has barely begun to tap the potential of these structures. Work till now have shown that they can pass through membranes, carrying therapeutic drugs, vaccines and nucleic acids deep into the cell to targets previously unreachable. This review attempts to understand the basics and summarize the most recent developments in the field of applied nanomaterials, in particular their application in biology and medicine, and discusses their commercialization prospects.